2019
DOI: 10.1007/s13659-019-0202-5
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal Investigation of Medicinal Plants of Chakrata Region (Uttarakhand) Used in the Traditional Medicine for Diabetes by Jaunsari Tribe

Abstract: The Himalayan region is the treasure house of natural wealth, particularly of medicinal and aromatic plants. These plants are used by the Indian traditional healers for the past many centuries to treat various ailments such as skin disorders, asthma, diabetes, snake bite, fever, pain, eye diseases, diarrhoea, indigestion, jaundice, burn, wound, liver disorder, CNS disorders and urinary tract infection. The indigenous traditional knowledge of medicinal plants and therapies of various local communities has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 110 publications
(151 reference statements)
0
18
0
Order By: Relevance
“…Field survey was conducted during the year between 2017 and 2020. A total of 8 visits of 3-5 days were conducted in the study area covering almost all the areas in different seasons included in our previous survey (Kumar et al 2019). The information about the local uses of these medicinal plants was collected from the local folk practitioners, cattle feeders and elder villagers.…”
Section: Methodsmentioning
confidence: 99%
“…Field survey was conducted during the year between 2017 and 2020. A total of 8 visits of 3-5 days were conducted in the study area covering almost all the areas in different seasons included in our previous survey (Kumar et al 2019). The information about the local uses of these medicinal plants was collected from the local folk practitioners, cattle feeders and elder villagers.…”
Section: Methodsmentioning
confidence: 99%
“…is widely used in Indian traditional medicine for the treatment of diabetes (Upwar et al, 2011), which is also reported in Ayurvedic Pharmacopoeia. The decoction (5-10 mL) of roots or stems of this species prepared with water was taken twice a day for 1-2 weeks to treat diabetes in Uttarakhand region (Kumar et al, 2019). It is also used by Uttarakhand people for the treatment of hypertension (Singh et al, 2019).…”
Section: Ethnopharmacology Of Berberis Spp Against Diabetes and Othementioning
confidence: 99%
“…Plant products are not only used in traditional medicine but are also in demand globally as potential sources for the development of new drugs [3]. The Indigenous traditional herbal remedies contain unique formulations of local herbs and herbal extracts that have been developed based on conventional knowledge and local wisdom [4][5][6].…”
Section: Introductionmentioning
confidence: 99%